STRATEGIES OF LEARNING ENGLISH APPLIED BY THE FIRST YEAR STUDENTS OF ENGLISH TEACHING DEPARTMENT OF STAIN MANDAILING NATAL - Sahyoni Sahyoni (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2020)
It is obvious that the use of learning strategy is a crucial element for EFL in studying English. Learning strategy becomes a tool for language learner in order to enhance their learning. An active application of language learning helps students in managing their own learning by developing language skill, increasing confidence and improving autonomous learning. Each of learners has different strategy to be applied in their classroom and daily life. The main objective of this study is to investigate the strategy of learning English conducted by the first year students of English teaching department of STAIN Mandailing Natal. This study was quantitative approach which carried out on the sample of 30 participants. All those participants are the first year students of English Teaching Department State College for Islamic Studies (STAIN) Mandailing Natal, Sumatera Utara. To obtain the data, researcher used two instruments namely: questionnaire and interview. The questionnaire consists of 26 questions which taken from blue print of strategy inventory for language learning (SILL). Interview is used to obtain deep and detail information about the application of learners’ learning strategy. Based on the data analysis, it is reasonable to state that most of the learners used metacognitive strategy in learning English as foreign language.